2007
DOI: 10.1007/s10482-006-9135-1
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the nitrogen source added to nitrogen depleted vinifications conducted by a Saccharomyces cerevisiae strain in synthetic must affects gene expression and the levels of several volatile compounds

Abstract: Nitrogen starvation may lead to stuck and sluggish fermentations. These undesirable situations result in wines with high residual sugar, longer vinification times, and risks of microbial contamination. The typical oenological method to prevent these problems is the early addition of ammonium salts to the grape juice, although excessive levels of these compounds may lead to negative consequences for the final product. This addition reduces the overall fermentation time, regardless of the time of addition, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 56 publications
4
44
0
Order By: Relevance
“…In addition, winemaking selection appeared to have specially targeted the acidic isoform of Tdh3p. In a recent work, JimenezMarti and coworkers suggested that Tdh3p might account for strain adaptation to enological conditions (84). This could explain why isoforms of this enzyme had been specially targeted for wine strains.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, winemaking selection appeared to have specially targeted the acidic isoform of Tdh3p. In a recent work, JimenezMarti and coworkers suggested that Tdh3p might account for strain adaptation to enological conditions (84). This could explain why isoforms of this enzyme had been specially targeted for wine strains.…”
Section: Discussionmentioning
confidence: 99%
“…Troubled fermentations have been attributed to the nutritional status of grape musts, once they contain suboptimal yeast nutrients, especially assimilable nitrogen 3,17,21,32 . A common practice in the wine industry for nitrogen limited fermentation is the addition of nitrogen supplements, using inorganic salts such as diammonium phosphate 22,27 .…”
Section: Discussionmentioning
confidence: 99%
“…completion and product quality 14,17,30,32 . The main sources of assimilable nitrogen in grape must are ammonium compounds, α-amino acids and to a lesser extent peptides 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen additions in the third stage of FSCF resulted in a substantial increase in the fermentation rate while biomass production was almost unaffected; this is consistent with previous observations during batch cultures (2,11,20). This recovery of an efficient fermentative activity has been explained by the increase of glucose uptake capacity, related to the de novo synthesis of glucose transporters (2,34,35,59). More generally, previous works reported that one of the main consequences of nitrogen supplementation during wine fermentation was an enhanced de novo synthesis of proteins, which involves an increase in the anabolism of amino acids (36,37).…”
Section: Figmentioning
confidence: 99%